1999
DOI: 10.1002/(sici)1099-1085(199905)13:7<1051::aid-hyp789>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The influence of recent environmental change on flooding and sediment fluxes in the Yorkshire Ouse basin

Abstract: This study attempts to establish causes of historical variations in¯ood frequency and magnitude in a 119-year ood stage record at York, and assess its likely eects on¯uxes of ®ne sediment and associated base metal contaminants. Climatic controls of¯ooding are evaluated through analysis of synoptic¯ood generation, and large-scale land use changes are also considered in terms of their in¯uence on food frequency and magnitude and sediment availability. The late nineteenth century was characterized by low¯ood freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The unclassified type (U) was not observed during the studied period. These results are in accordance with LCT frequencies assessed in previous studies for UK (Longfield and Macklin, 1999;Pattison and Lane, 2012) and Sweden (Chen, 2000). LCC A is similarly dominant with over 30%, and LCCs W and C have very similar frequencies.…”
Section: Lamb Circulation Types and Classessupporting
confidence: 92%
See 1 more Smart Citation
“…The unclassified type (U) was not observed during the studied period. These results are in accordance with LCT frequencies assessed in previous studies for UK (Longfield and Macklin, 1999;Pattison and Lane, 2012) and Sweden (Chen, 2000). LCC A is similarly dominant with over 30%, and LCCs W and C have very similar frequencies.…”
Section: Lamb Circulation Types and Classessupporting
confidence: 92%
“…Several studies focusing on the relationship between largescale atmospheric circulation and precipitation extremes have used the LCT classification; Trigo and DaCamarra et al (2000) in Portugal, Linderson (2001) in Sweden, Post et al (2002) in Estonia, Fernández-González et al (2012) in Spain and Jones et al (2014) in UK. Additionally, analyses on the relationship between river discharge and LCTs have been conducted (Longfield and Macklin, 1999;Pattison and Lane, 2012). In the study by Schiemann et al (2009), the LCT classification showed an average predictive skill for precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in flooding recorded in Yorkshire Ouse catchment since the 1980s (Longfield and Macklin, 1999) is also evident in other parts of northern (Werritty, 2002) and western Britain (Higgs, 1987). In the upper Severn basin, mid-Wales, for example, increased flooding has resulted in higher bank erosion rates and larger areas of gravel within the channel, stored within periodically mobile gravel-bar complexes (Gittins, 2004).…”
Section: 'Little Ice Age' Flooding and Alluvial Responses To Modern Cmentioning
confidence: 88%
“…Whether the floods experienced in recent years in Germany and in other European countries are triggered or worsened by human activities has been the subject of a great deal of debate. (1)(2)(3)(4)(5) Possible anthropogenic activities leading to increased flood risk include river regulation measures, intensified land use and forestry, and emissions of greenhouse gases causing a change in the global climate. This article discusses the latter by reviewing the existing knowledge on the subject.…”
Section: Introductionmentioning
confidence: 99%